Chronic fluoxetine administration enhances synaptic plasticity and increases functional dynamics in hippocampal CA3-CA1 synapses. (November 2017) - Popova, Dina; Castrén, Eero; Taira, Tomi
Abstract: Recent studies demonstrate that chronic administration of the widely used antidepressant fluoxetine (FLX) promotes neurogenesis, synaptogenesis and synaptic plasticity in the adult hippocampus, cortex and amygdala. However, the mechanisms underlying these effects and how are they related to the clinical antidepressant efficacy are still poorly understood. We show here that chronic FLX administration decreases hippocampus-associated neophobia in naïve mice. In parallel, electrophysiological recordings in hippocampal CA3-CA1 circuitry revealed that the FLX treatment resulted in increased short- and long-term plasticity likely attributed to changes in presynaptic function. These changes were accompanied by enhancement in the expression of proteins related to vesicular trafficking and release, namely synaptophysin, synaptotagmin 1, MUNC 18 and syntaxin 1. Thus, chronic FLX administration is associated with enhanced synaptic dynamics atypical of mature CA1 synapses, elevated hippocampal plasticity, improved hippocampus-dependent behavior as well as altered expression of synaptic proteins regulating neurotransmitter trafficking and release. The results support the idea that antidepressants can promote neuronal plasticity and show that they can increase the functional dynamic range and information processing in synaptic circuitries. Highlights: Antidepressant fluoxetine promotes synaptic dynamics atypical for mature CA3-CA1 synapses. Fluoxetine accentuates long term synaptic plasticity and induces parallel changes in neophobic behavior in mice. Chronic fluoxetine induces changes in the expression of proteins regulating vesicular trafficking and transmitter release.